Changing Pattern of World Trade and Role of Global Supply Chains: Evidences from Recent Literature - Singh, Kulwinder; Kaur, Simran; Shalu, Kumari (Gyan Management Journal, 2023)
Recent developments in the world economy have substantially increased interdependence among nations, due to which no nation can isolate itself completely from the rest of the world. Internationalization of production has resulted to mutual exchange of goods, services, technologies, people and investment, generally called as supply-chain trade. These processes have dramatically influence structure of production networks in global economy. Traditional domestic production networks have been replaced by much modernized global ones. The trade that is taking place through international networks is associated with momentous of global economic changes. These global supply networks have several economic and non economic effects particularly on the business organization involved and generally on the economies/nations as a whole. Trading pattern of world economy has also experiencing changes under the influence on these supply chains. This paper highlights the role of recent global supply chains in changing pattern of world trade. Evidences from literature reveal that recent global supply chains have had a significant effect on pattern of world trade as Newly Emerging Economies (EMEs) are emerging as manufacturing trading partners which was not even dreamt about few years back during 1970s and 1980s. Role of supply chain to make these changes incidental is multidimensional and immense. Paper also highlights role of transnational corporations (TNCs) in coordinating global trade through creation of global supply chains and importance of these chains as instrument of trade policies for firms in developing nations.